Future and career plans before high school graduation (ZuBAb): Background, research questions and research design - Irena Pietrzyk; Jutta Allmendinger; Melinda Erdmann; Marcel Helbig; Marita Jacob; Stefan Stuth (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
The German educational system is characterized by pronounced educational disparities based on the parental socioeconomic status. Despite the rather strong stratification of the secondary school sys-tem and social selection into obtaining the university entrance qualification, the transition to higher education is no exception to the general picture of strong inequalities in the German educational system. Social differences in enrolment in higher education might be partly due to the unequal distribution of information and differences in social support. If this were the case, offering information and support via guidance counsellors could reduce educational disparities in the transition to higher education. However, empirical research on this issue in Europe, especially in Germany, is scarce. Against this background, the study "Future and Career Plans Before High School Graduation" (in German: Zukunfts- und Berufspläne vor dem Abitur, ZuBAb) investigates how a broad long-term counselling program affects the educational pathways of university-eligible students by means of a randomized controlled trial (RCT). The study focuses on the reduction of inequalities in university enrolment (primary outcome). Furthermore, we examine the effect of the intervention on the development of socio-emotional competencies, choice of study majors, satisfaction with educational choices, congruence between occupational interests and educational choice, and rational choice components (secondary outcomes). In addition to investigating the effect of the program on educational pathways by means of an RCT, we analyse the social composition of participating students under real world conditions to estimate the effectiveness of the program in reducing educational disparities under real world conditions. The present discussion paper provides an overview of the background of the ZuBAb study, the research questions that are addressed, and the research design. The study is currently being conducted. It is funded by the Ministry of Culture and Science of the German State of North Rhine-Westphalia. Research is jointly carried out by the Berlin Social Science Centre and the University of Cologne.
Keywords: 300; educational inequality; educational intervention; randomized controlled trial (RCT)